2005
DOI: 10.4049/jimmunol.175.7.4745
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Hepatocyte Growth Factor as an Immune Regulator through Suppressing Dendritic Cell Function

Abstract: Hepatocyte growth factor (HGF) plays an important role in many biological events such as angiogenesis, cell proliferation, anti-fibrosis and antiapoptosis. It is well known that HGF promotes tumor progression and suppresses development of fibrosis after tissue injury. In contrast, its role in immune-mediated disorders has not been fully clarified. In the present study, we examined the role of HGF in Ag-specific immune response using in vitro studies and an experimental model of allergic airway inflammation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
205
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(220 citation statements)
references
References 52 publications
10
205
2
3
Order By: Relevance
“…Third, although admittedly still debated in terms of prevalence, individuals with autism can present complex medical profiles, such as gastrointestinal, immune, and nonspecific neurological dysfunctions (14,15). In addition to brain development, the pleiotropic MET receptor tyrosine kinase has specific roles in digestive system development and repair (18,23,24) and modulation of T cell-activated peripheral monocytes and dendritic antigen-presenting cells (20,22). We raise the possibility, still to be tested, that increased risk for autism, due to a functional polymorphism in the MET gene, may impart in certain individuals shared etiology of a parallel, although independent, disruption of brain and peripheral organ development and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, although admittedly still debated in terms of prevalence, individuals with autism can present complex medical profiles, such as gastrointestinal, immune, and nonspecific neurological dysfunctions (14,15). In addition to brain development, the pleiotropic MET receptor tyrosine kinase has specific roles in digestive system development and repair (18,23,24) and modulation of T cell-activated peripheral monocytes and dendritic antigen-presenting cells (20,22). We raise the possibility, still to be tested, that increased risk for autism, due to a functional polymorphism in the MET gene, may impart in certain individuals shared etiology of a parallel, although independent, disruption of brain and peripheral organ development and function.…”
Section: Discussionmentioning
confidence: 99%
“…MET is best understood for its role in the metastasis of a variety of cancers (16), due to somatic gain-of-function mutations, and in mediating hepatocyte growth factor (HGF)͞scatter factor signaling in peripheral organ development and repair (17)(18)(19). MET signaling contributes to immune function (20)(21)(22) and gastrointestinal repair (18,23,24). Recent studies by our group and others revealed that MET also contributes to development of the cerebral cortex (25,26) and cerebellum (27), both of which exhibit developmental disruptions in autism (28,29).…”
mentioning
confidence: 99%
“…Within the hematopoietic compartment, c-Met is found constitutively expressed on progenitor cells and their Agpresenting progeny, including DCs, but is absent from T cells (6). Originally identified as a mitogen for hepatocytes, HGF acts as a potent regulator in multiple animal models of immunemediated disorders (7)(8)(9)(10), which suggests that HGF regulates key inflammatory events that are common to many diseases and organ systems. In particular, HGF has been demonstrated to re-strain the Ag-presenting function of mouse DCs (7) and to govern the development of Treg cell-inducing regulatory DCs (11,12).…”
Section: Ultiple Sclerosis (Ms) Is a Chronic Disorder Character-mentioning
confidence: 99%
“…Originally identified as a mitogen for hepatocytes, HGF acts as a potent regulator in multiple animal models of immunemediated disorders (7)(8)(9)(10), which suggests that HGF regulates key inflammatory events that are common to many diseases and organ systems. In particular, HGF has been demonstrated to re-strain the Ag-presenting function of mouse DCs (7) and to govern the development of Treg cell-inducing regulatory DCs (11,12). We recently suggested that such a mechanism might account for the protective role of CNS-restricted overexpression of HGF in myelin oligodendrocyte glycoprotein (MOG)-induced EAE (11).…”
Section: Ultiple Sclerosis (Ms) Is a Chronic Disorder Character-mentioning
confidence: 99%
“…Studies show that MSC can suppress macrophage trans-differentiation to inflammatory phenotypes [22], inhibit DC maturation and migration, and halt inflammatory cytokine generation from leukocytes [22][23][24]. HGF is immunoregulatory and reduces inflammatory cytokine generation from DCs [25]. IGF-1 blocks not only the early onset of apoptosis, but also inflammation and accompanying tissue injury [26].…”
Section: Introductionmentioning
confidence: 99%